2019
DOI: 10.20307/nps.2019.25.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antimicrobial Efficiency of Swietenia macrophylla Seed Extract on Clinical Wound Pathogens

Abstract: Microbial wound infection prolonged the hospitalization and increase the cost for wound management. Silver is commonly used as antimicrobial wound dressing. However, it causes several adverse side effects. Hence, this study was aimed to evaluate the antimicrobial efficiency of Swietenia macrophylla seed extract on clinical wound pathogens. Besides, the bioactive constituents of the seed extract were also determined. S. macrophylla seeds were extracted with methanol by maceration method. The seed extract inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Next, methanol extract of S. macrophylla seeds inhibited the growth of five different bacteria species and one yeast. These microorganisms were Acinobacter anitratus, S. aureus, Bacillus cereus, Bacillus subtilis, Shigella boydii, and Candida utilis [19]. Again, E. coli was not reported to be inhibited by this particular extract, which is the opposite to another study that also used methanol as the extracting solvent [19,20].…”
Section: An Antimicrobial Remedy Against Skin Disordersmentioning
confidence: 64%
See 2 more Smart Citations
“…Next, methanol extract of S. macrophylla seeds inhibited the growth of five different bacteria species and one yeast. These microorganisms were Acinobacter anitratus, S. aureus, Bacillus cereus, Bacillus subtilis, Shigella boydii, and Candida utilis [19]. Again, E. coli was not reported to be inhibited by this particular extract, which is the opposite to another study that also used methanol as the extracting solvent [19,20].…”
Section: An Antimicrobial Remedy Against Skin Disordersmentioning
confidence: 64%
“…These microorganisms were Acinobacter anitratus, S. aureus, Bacillus cereus, Bacillus subtilis, Shigella boydii, and Candida utilis [19]. Again, E. coli was not reported to be inhibited by this particular extract, which is the opposite to another study that also used methanol as the extracting solvent [19,20]. In an article written by Durai and team [20], both S. aureus, E. coli, and three other fungi (Fusarium sp., Alternaria sp., and Helminthosporium sp.)…”
Section: An Antimicrobial Remedy Against Skin Disordersmentioning
confidence: 86%
See 1 more Smart Citation
“…The MBC values against S. pneumoniae, B. cereus, and C. sporogenes were found to be greater than 1000 μg/mL while the MBC value against S. aureus jms.mabjournal.comAmran et al, 2023 Malaysian Applied Biology was 1000 μg/mL. A previous study byGopalan et al (2019) showed the lowest MIC value of S. macrophylla seed extract was recorded against B. subtilis (1.56 mg/mL), followed by B. cereus (3.13 mg/mL). In 2009, Tan et alshowed a good inhibitory effect of methanolic extracts of S. macrophylla leaves against B. subtilis and S. aureus with larger inhibition zones as compared to gentamicin.…”
mentioning
confidence: 88%
“…According to Mohammed et al (2014), the growth of E. coli and P. aeruginosa were inhibited by seeds and leaves extracts of S. macrophylla at 25 and 50 mg/mL respectively. Gopalan et al (2019) demonstrated that the MBC value of Swietenia macrophylla seed extract against Gram-negative bacteria, Shigella boydii, and Acinetobacter anitratus, was 25 mg/mL respectively. Meanwhile, the antibacterial activities of petroleum ether and ethanolic extract of S. macrophylla leaves are due to the presence of terpenoids (Ayyappadhas et al, 2012).…”
Section: Mic and Mbcmentioning
confidence: 99%